Dielectric properties of BADCy/Ni0.5Ti0.5NbO4 composites with novel structure fabricated by freeze casting combined with vacuum assisted infiltration process. (23rd November 2015) - Zhang, Biao; Ye, Feng; Gao, Ye; Liu, Qiang; Liu, ShiChao; Liu, Limeng
Abstract: Bisphenol-A cyanate ester resin (BADCy)/Ni0.5 Ti0.5 NbO4 composites with novel structure, within which Ni0.5 Ti0.5 NbO4 and BADCy are continuous directional distribution and parallel to the electric field direction (marked as composite-directional), were designed and fabricated using freeze casting combined with vacuum assisted infiltration process. Dielectric properties as well as the moisture absorption of the composites were studied. Theoretical models used to predict the dielectric properties of the composites were established. Results show that the novel structure can significantly improve the dielectric constant while decrease dielectric loss compare with traditional structure in which Ni0.5 Ti0.5 NbO4 filler is homogeneously distributed (the composite marked as composite-homogeneous). Dielectric constant of composite-directional is as high as 19.93 while dielectric loss is only 4.07 × 10 −3 (at 7319 MHz) when Ni0.5 Ti0.5 NbO4 content is 43.79 vol%. Furthermore, the dielectric constant of both composite-directional and composite-homogeneous can be predicted using Rother-Lichtenecker model when the fitting parameters ( n ) are −0.5188 and −0.1499, respectively. Distribution state of Ni0.5 Ti0.5 NbO4 is the main reason for the difference of fitting parameters. Due to the excellent properties of composite-directional, this kind of composites can be used as printed circuit board (PCB) materials.